GÊNERO E PODER: MULHERES DOCENTES EM INSTITUIÇÕES TEOLÓGICAS PROTESTANTES DA GRANDE SÃO PAULO - Souza, Adriana de (2006)
The theme of this work, Gender and Power in Protestant Theological Institutions in Greater São Paulo , problematizes the gendered social reality faced by the men and women educated in these institutions. An initial premise is that the power relations emerging in this institutional context ghettoize women in educational trajectories labeled as feminine , a development implicit in a set of social representations that justify this stereotyping of academic paths and naturalization of disparities, given that power continually makes use of difference to underwrite forms of domination and supremacy, in this case of men over women. Gender is a central category given the attempt to uncover the means by which the knowledges and practices produced in this context are strictly related to the social production of femininity and masculinity considered to be atemporal and permanent categories and of the power relations endemic to the institution. In this religion system, political relations involve a constant dialectic between Seminary and Church, in which the power of the latter legitimizes the forms of exclusion imposed by the former. Although formal differences remain, forms of resistance always arise in the face of domination, especially given the subtlety with which they establish themselves. Women s presence in the Seminaries, unusual until recently, can be read in terms of strategies of breaking down domination, offering a secure means of entering an essentially masculine space.